Influence of the rapid thermal treatment of the initial silicon wafers on the process of their pyrogenic oxidation - Anishchik, Victor M.; Harushka, Valiantsina A.; Pilipenka, Uladzimir A.; Ponariadov, Vladimir V.; Saladukha, Vitali A. (Journal of the Belarusian State University. Physics, 2019)
The work represents the investigation results of influence of rapid thermal treatment of the initial silicon wafers on the process of their pyrogenic oxidation. It is shown that the given treatment results in the quality enhancement of silicon dioxide, formed on their surface owing to thickness reduction of the disrupted layer, substantially influencing the initial stage of the oxidation process.
Keywords: rapid thermal treatment; disrupted layer; pyrogenic oxidation; refraction ratio